Sensitivity and specificity of the Posttraumatic Stress Disorder Checklist for DSM‐5 in a Canadian psychiatric outpatient sample. Issue 2 (17th November 2021) - Boyd, Jenna E.; Cameron, Duncan H.; Shnaider, Philippe; McCabe, Randi E.; Rowa, Karen
Abstract: The Posttraumatic Stress Disorder (PTSD) Checklist for DSM‐5 (PCL‐5) is a widely used, self‐report measure that is employed to assess PTSD symptom severity and determine the presence of probable PTSD in various trauma‐exposed populations. The PCL‐5 is often administered in clinical settings as a screening tool for PTSD, with a suggested cutoff score of 33 indicating a probable PTSD diagnosis. Recent research indicates that a higher cutoff may be required in psychiatric samples. In the present study, we aimed to determine the sensitivity and specificity of the PCL‐5 in a Canadian outpatient psychiatric sample and establish an optimal cutoff score for detecting probable PTSD in this sample. Participants were 673 individuals who reported a history of trauma exposure and were assessed using a semistructured interview and self‐report measures. Individuals diagnosed with PTSD ( N = 193) reported a mean PCL‐5 score of 56.57, whereas individuals without PTSD ( N = 480) reported a mean score of 33.56. A score of 45 was determined to be the optimal cutoff score in this sample, balancing sensitivity and specificity while detecting a probable diagnosis of PTSD. Consistent with findings in other psychiatric samples, these findings indicate that in an outpatient psychiatric sample with a history of exposure to a variety of trauma types, a higher cutoff score is required to determine probable PTSD. In addition, given the estimated rate of false positives even with a higher cutoff, follow‐up diagnostic assessments are recommended.